Severe atopic dermatitis is associated with a reduced frequency of IL-10 producing allergen-specific CD4+ T cells. - Seneviratne, S; Jones, L; Bailey, A; Black, A; Ogg, G (2006)
BACKGROUND: Several studies have investigated levels of T-cell-derived interleukin (IL)-10 in individuals with atopic dermatitis, with conflicting results. AIMS/HYPOTHESIS: In order to address whether stratification of disease severity may help resolve the different findings, the hypothesis was tested that individuals with severe atopic dermatitis have a lower frequency of circulating IL-10-producing, allergen-specific CD4+ T cells than do individuals with mild disease. METHODS: Using peripheral blood mononuclear cells derived from individuals with severe (n=12) and mild atopic dermatitis (n=10) and from nonatopic controls (n=10), we investigated production by CD4+ T cells of tumour necrosis factor (TNF)-alpha, IL-4, IL-5, IL-13 and IL-10 in response to phorbol myristate acetate/ionomycin and Der p1 allergen. RESULTS: It was observed that there were significantly higher frequencies of allergen-specific circulating CD4+ T cells producing TNF-alpha- IL-4-, IL-5- and IL-13, and lower frequencies of these cells producing IL-10 in individuals with severe atopic dermatitis compared with mildly affected individuals and nonatopic controls (P<0.01 for all comparisons). Furthermore, the Der p1-specific CD4+ T cells were enriched within the subset of cells positive for cutaneous lymphocyte-associated antigen. CONCLUSIONS: Analysis of levels of allergen-specific CD4+ T-cell production of IL-10 in relation to disease severity argues in favour of a role for IL-10 in the control of atopic dermatitis.